Exploring the supportive care needs for people with cancer undergoing chemotherapy: a qualitative descriptive study - A'la, Muhamad Zulfatul; Nuntaboot, Khanitta (Jurnal Ners, 2023)
Introduction: Chemotherapy's side effects cause people with cancer to encounter difficult situations that might impact their supportive care needs. Exploration of supportive care needs may assist the nurse in improving the quality of life of people with cancer undergoing chemotherapy (PwCUC). Therefore, this study aims to explore the supportive care needs of PwCUCs. Methods: A qualitative descriptive study from November 2021 until May 2022 was utilized through in-depth interviews and Focus Group Discussions (FGD) in three public health centers in Jember, Indonesia. Data saturation was achieved after the researcher conducted an in-depth interview of 27 informants and FGD of 13 informants. A total 40 informants from PwCUCs, family of PwCUCs, doctors, and nurses was recruited based on inclusion criteria using purposive sampling technique. The researcher developed an in-depth interview and FGD guidelines to collect the data. Six-step thematic analysis was used. Triangulation, member-checking, and thick description were performed to maintain trustworthiness. Results: The study yielded four themes that represent participants' voices. These were 1) social support needs, 2) accompanying needs, 3) information needs, and 4) healthcare service support. Conclusion: Supportive care needs for PwCUCs is a complex and contextual phenomenon. This study revealed that PwCUCs required individual, social, and healthcare service support to meet their needs. Therefore, further study is required regarding developing a nursing care plan for PwCUCs based on cultural-sensitive supportive care needs.